Trajetória metodológica voltada para superação de problemas pedagógicos, a partir da análise dos dados do SARESP e da Avaliação da Aprendizagem em Processo AAP - Guellere, Edna Caldeira Martins (2015)
The role of a teaching supervisor, in a school administration scenario, brings about the need to introduce a project for analyzing internal and external assessment results, as state public schools in São Paulo take part in official assessments on a regular basis São Paulo Student Performance Assessment System (Sistema de Avaliação do Rendimento Escolar de São Paulo - SARESP) and Learning Assessment in Process (Avaliação da Aprendizagem em Processo - AAP) producing information to improve students learning. However, most of the schools do not take advantage of these data yet, chiefly when members of the school administration do not consider their potential for making important decisions. Thus, the main aim of this study is to contribute to teachers reflective process on assessment practices based on students achievement data. For this purpose, the methodology relies on action research and the objectives involve the analysis of issues related to assessment results, along with school managers, in order to direct the routine work of the teaching supervisor in promoting a process of problematization by examining the results obtained from SARESP, AAP and school internal assessments, leading to improvements in teaching and learning practices. The theoretical basis is originated from Sousa (2000); Bolivar (2003); Tedesco (2004); Saul (2008) and Bonamino & Souza (2012) support reflections on assessment system as a process of evaluation for collaborative decision-making so that participants may be engaged and responsible for the quality of education in school. In order to consider SARESP as an assessment system, it was required to analyze the works of Freire (2008); Arcas (2009); Machado (2010) and Pimenta (2012),giving rise to the idea that there is a real need to encourage the discussion on how to take advantage of the assessment data available. SARESP delivers standardized reports that identify students performance indicators, but that data may become of no practical use if all participants in the teaching and learning process do not recognize and understand them as resources for decision making. By analyzing the perceptions of interviewed individuals and policy documents, it was possible to discover that AAP can be considered as an internal assessment. The baseline information from Hadji (2001); Gatti (2003); Hoffman (2003) e Luckesi (2008) were fundamental for understanding that the evaluation process is also a formative one for every individual involved in educational practices. As an outcome, the elaboration of a roadmap is proposed for the use of assessment results obtained from SARESP, AAP and teachers assessment practices. It is believed that the roadmap is able to support teaching supervisors and school managers decisions concerning the improvement of the teaching and learning process